2015
DOI: 10.1155/2015/315219
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Percutaneous Electrolysis and Eccentric Exercises for Subacromial Pain Syndrome: A Randomized Clinical Trial

Abstract: Objective. To compare effects of ultrasound- (US-) guided percutaneous electrolysis combined with an eccentric exercise program of the rotator cuff muscles in subacromial pain syndrome. Methods. Thirty-six patients were randomized and assigned into US-guided percutaneous electrolysis (n = 17) group or exercise (n = 19) group. Patients were asked to perform an eccentric exercise program of the rotator cuff muscles twice every day for 4 weeks. Participants assigned to US-guided percutaneous electrolysis group al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(123 citation statements)
references
References 26 publications
4
108
0
11
Order By: Relevance
“…With subsequent eccentric work, the tissue is stimulated to give mechanical support to the biological treatment. Arias-Buría et al showed poor results with the use of electrolysis in tendinopathies of the supraspinatus (31).…”
Section: Discussionmentioning
confidence: 99%
“…With subsequent eccentric work, the tissue is stimulated to give mechanical support to the biological treatment. Arias-Buría et al showed poor results with the use of electrolysis in tendinopathies of the supraspinatus (31).…”
Section: Discussionmentioning
confidence: 99%
“…The galvanic current in a saline solution rapidly develops the chemical process of electrolysis, which in turn in-duces tissue ablation 11 . The EPI technique finds indications in the treatment of tendinopathies and fibrosis [12][13][14][15][16] . The rationale for using EPI in the treatment of PH-TrSNE is the ability of the technique to specifically degrade fibrotic adhesions that bind the SN and SM tendon.…”
Section: Ultrasound-guided Intratissue Percutaneous Electrolysismentioning
confidence: 99%
“…To date however, few studies have tested the effectiveness of the technique. The therapeutic utility of EPI (by some Authors replaced with the acronym PNE, Percutaneous Needle Electrolysis) was tested for the treatment of patellar tendinopathy 12,13 , sub-acromial syndrome 14 , chronic lateral epicondylitis 15 and rectus abdominisrelated groin pain 16 . The clinical results presented in this work are somewhat in conflict, especially given the different methodological choices of the Authors, in particular relative to the intensity and duration of administration of the galvanic current (which varied from 0.3 mA for 1.2 minutes to 3 mA for a few seconds) and suggested physiotherapy administered in combination with the technique.…”
Section: Ultrasound-guided Epi In the Treatment Of Tendinopathiesmentioning
confidence: 99%
“…The galvanic current in a saline solution rapidly develops the chemical process of electrolysis, which in turn induces tissue ablation 11 . The EPI technique finds indications in the treatment of tendinopathies and fibrosis [12][13][14][15][16] . The rationale for using EPI in the treatment of PHTrSNE is the ability of the technique to specifically degrade fibrotic adhesions that bind the SN and SM tendon.…”
Section: Ultrasound-guided Intratissue Percutaneous Electrolysismentioning
confidence: 99%